A Comparativestudy On Present Education System In Haryana And Its Neighbouring States - GULIA, DR. SUMAN (The journal of contemporary issues in business and government, 2021)
India has the second largest education system in the world. The Indian education system has gone through many phases. Great effort has been put to shape up the present scenario of education system. The announcements like abolishing compulsory CBSE board exams for class 10th from the session 2010-11, introduction of grading system, the passage of Right of Children to free and Compulsory Education Bill, reservation policies etc. Are a few among them? Now the question arises as to what extent such efforts in the field of education have succeeded in different states of the country. Haryana is the state with a contribution of 3.7% in the total GDP of India. This present study will throw light on the education system of Haryana, with a comparative eye on its neighbouring states. An analysis of the educational achievements of these states from different angles will help the experts and the researchers to know how far we have gone in achieving our targets and what needs to be done. This paper is descriptive in nature, based on the data collected from different websites of ministry as well as reports of planning commission.